Max's New Baby - Steel, Danielle; Rogert, Jacqueline (New York Doubleday, 1989)
Unsure about the prospect of having a new baby in the house, four-and-a-half-year-old Max finally decides that it might not be so bad after all.
purchased, 8/97
Keywords: Babies -- Fiction; Brothers and sisters -- Fiction; Family life -- Fiction